2017
DOI: 10.1371/journal.pone.0179558
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol esterification inhibition and imatinib treatment synergistically inhibit growth of BCR-ABL mutation-independent resistant chronic myelogenous leukemia

Abstract: Since the advent of tyrosine kinase inhibitors (TKIs) such as imatinib, nilotinib, and dasatinib, chronic myelogenous leukemia (CML) prognosis has improved greatly. However, ~30–40% of patients develop resistance to imatinib therapy. Although most resistance is caused by mutations in the BCR-ABL kinase domain, 50–85% of these patients develop resistance in the absence of new mutations. In these cases, targeting other pathways may be needed to regain clinical response. Using label-free Raman spectromicroscopy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 25 publications
1
34
0
Order By: Relevance
“…Developing inhibitors against CE is of high clinical interest (Table 1). In an imatinib-resistant chronic myelogenous leukaemia cell line, inhibition of CE by the ACAT1 inhibitor avasimibe suppresses tumour growth and subsequently restores imatinib sensitivity by downregulating MAPK signaling 110 . In prostate cancer, avasimibe treatment impairs the Wnt-β-catenin pathway and thus suppresses metastasis 111 .…”
Section: Enhancement Of Cd8 T Cell Function and Inhibition Of The Regmentioning
confidence: 99%
“…Developing inhibitors against CE is of high clinical interest (Table 1). In an imatinib-resistant chronic myelogenous leukaemia cell line, inhibition of CE by the ACAT1 inhibitor avasimibe suppresses tumour growth and subsequently restores imatinib sensitivity by downregulating MAPK signaling 110 . In prostate cancer, avasimibe treatment impairs the Wnt-β-catenin pathway and thus suppresses metastasis 111 .…”
Section: Enhancement Of Cd8 T Cell Function and Inhibition Of The Regmentioning
confidence: 99%
“…Recent studies have identified an aberrant accumulation of cholesteryl ester (CE) mediated by the enzyme Acyl coenzyme A: cholesterol acyltransferase 1 (ACAT-1) in multiple cancers, including prostate, pancreatic, leukemia, glioma, breast, colon and lung cancer [ 16 22 ]. Inhibition of ACAT-1 using a small molecule inhibitor, avasimibe, effectively removed CE accumulation and suppressed tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…BrA was less potent than the prototypical ACAT inhibitor Sah 58-035 but more potent than two other pentacyclic terpenoids betulinic acid and ursolic acid that are well studied for their pharmacological properties [ 7 , 44 , 45 ]. Although ACAT inhibition was earlier used to screen compounds with steroidal backbones for putative antiatheromatous properties [ 31 ], recent data from the literature showed that cholesteryl esters of fatty acids displayed tumour promoter properties and that ACAT inhibition in cancer cells blocked cancer cell invasiveness and clonogenicity and activate the lymphocyte T CD8+ antitumor activity [ 13 , 18 , 27 , 29 , 30 , 35 , 36 ]. We report here for the first time that BrA displays ACAT inhibition and inhibits cancer cell clonogenicity and invasiveness.…”
Section: Resultsmentioning
confidence: 99%
“…These pathways include the oestrogen receptor alpha (ERα), cholesterol-5,6-epoxide hydrolase (ChEH) and acyl-co-A cholesterol acyl transferase (ACAT). The ACAT catalysed the esterification of cholesteryl esters with fatty acids and these fatty acid:cholesteryl esters were recently shown to act as tumour promoters making ACAT a new target in cancer research [ 13 , 18 , 25 , 27 , 28 , 29 , 30 ]. We report that BrA displayed anticancer properties through the inhibition of cholesterol esterification.…”
Section: Introductionmentioning
confidence: 99%